España y los Objetivos de Desarrollo del Milenio - Pajín Iraola, Leire (Revista Española de Desarrollo y Cooperación, 2023)
In this article, the Secretary of State for the International Cooperation reaffirms the commitment of the spanish government with the achievement of Millennium Development Goals, and analyzes the way followed by the spanish cooperation to contribute to them, principally the goal number 8: to promote a World Association for Development.